Mental Health Needs of Brazilian Immigrant Adolescents in the Greater-Boston Area: An Exploratory Qualitative Study - Rocha, Leticia P. (Tufts Archival Research Center, 2020)
Brazilians are a growing population in the Greater Boston area (up to 300,000), yet few studies have been conducted on this community. In one study related to adult Brazilian mental health, 35% of participants reported depressive symptomatology. This and significant gaps in literature, provide compelling reasons for further exploration of mental health among Brazilian immigrant youth.Methods: In order to understand the mental health needs of Brazilian immigrant adolescents in the Greater Boston area, semi-structured interviews (n=10) were conducted with leaders and representatives of organizations that serve the Brazilian community and work closely with adolescents.Results: Anxiety, depression, and substance abuse emerged as highly prevalent concerns among all participants. Interviewees identified immigration stressors, cultural conflicts, and different generational perceptions on mental health as negative factors associated with mental health issues. Protective factors were also identified, namely greater access to resources compared to immigrant adults and the cultural value of importance of family. Participants believe that Brazilian adolescents do not have sufficient access to treatment.Implications: This study reflects potential mental health vulnerabilities and considerations specific to the Brazilian immigrant population, with immigration stressors and cultural factors that should be addressed in relation to mental health. Future directions and the development of interventions are discussed.